2022
DOI: 10.1155/2022/1702819
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk of Lung Cancer in Tuberculosis Patients, and Vice Versa: A Literature Review of the Last Decade

Abstract: Background. The incidence and risk of both lung cancer (LC) and tuberculosis (TB) are increasing rapidly. These two diseases frequently exist together and can influence the incidence and risk of each other. The aim of the current review was to summarize the incidence and risk of LC in TB patients, and vice versa, short out research gap, and contemplate future research perspectives. Methodology. PubMed and Scopus databases, and Google Scholar search engine were searched for epidemiological studies that investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Analysis of the clinical characteristics of patients with LC-PTB and its subgroups, LC-APTB and LC-IPTB, revealed key ndings. Firstly, demographic characteristics showed that the median age of the LC-PTB group was 64 years, with a predominance of males and a widespread history of smoking, consistent with the literature suggesting that lung cancer with concurrent tuberculosis is common in older males who smoke [12][13][14] . Additionally, we found that the median age of LC-IPTB patients was slightly greater than that of LC-APTB patients, suggesting15 that younger LC patients might be more prone to active pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 79%
“…Analysis of the clinical characteristics of patients with LC-PTB and its subgroups, LC-APTB and LC-IPTB, revealed key ndings. Firstly, demographic characteristics showed that the median age of the LC-PTB group was 64 years, with a predominance of males and a widespread history of smoking, consistent with the literature suggesting that lung cancer with concurrent tuberculosis is common in older males who smoke [12][13][14] . Additionally, we found that the median age of LC-IPTB patients was slightly greater than that of LC-APTB patients, suggesting15 that younger LC patients might be more prone to active pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 79%
“…A reverse reaction is the development of a neoplasm and treatment that can induce the reactivation of latent infection with tuberculosis [ 25 , 26 ]. Bhowmik et al [ 27 ] found a 1.64- to 6-fold higher incidence and risk of lung cancer in patients with tuberculosis in comparison with patients without this medical condition. The authors also remarked that both of these diseases are often concomitant and the more frequent occurrence of lung cancer, as well as the lowered immunity due to lung cancer, can predis-pose to infection with Mycobacterium tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis bias and late treatment strategies for TB might be factors responsible for the high co-occurrence of TB and LC (8)(9)(10)(11). TB diagnosis is performed by QuantiFERON-TB Gold In-Tube tests as a gold standard (5,12).…”
Section: Introductionmentioning
confidence: 99%